Wireless, Battery‐free, Implantable Inductor‐Capacitor Based Sensors - Baochun Xu; Cunjiang Yu (Advanced Electronic Materials, 2025)
Abstract The growing demand for reliable and minimally invasive health monitoring technologies has driven the development of advanced implantable devices. Traditional systems relying on batteries and wires face challenges such as limited lifespan, complexity, and risks of complications. Inductor‐capacitor (LC) sensors offer a compelling alternative that uses simple resonant circuits to achieve battery‐free and wireless operation. These sensors function through magnetic coupling with external readers, eliminating the need for internal power sources or physical connections, while enabling compact and biocompatible designs. This review begins by introducing the fundamental principles and key design considerations of LC sensors, including material selection, geometric constraints, and implantation methods. It then examines their examplary applications, such as intracranial pressure monitoring, intraocular pressure measurement, tissue mechanics assessment, and tumor microenvironment analysis among others. Finally, this review discusses the challenges and future directions for implantable LC sensor technologies, emphasizing the importance of mechanism and material innovation, scalability and multifunctionality, and integration with digital healthcare systems to meet the demands of health monitoring.